A Novel Micellar Electrokinetic Chromatographic Method for Separation of Metal-DDTC Complexes - Arfana Mallah; Saima Q. Memon; Amber R. Solangi; Najma Memon; Kulsoom Abbassi; Muhammad Yar Khuhawar (The Scientific World Journal)
Micellar electrokinetic chromatography (MEKC) was examined for the separation and determination of Mo(VI), Cr(VI), Ni(II), Pd(II), and Co(III) as diethyl dithiocarbamate (DDTC) chelates. The separation was achieved from fused silica capillary (52 cm × 75 𝜇m id) with effective length 40 cm, background electrolyte (BGE) borate buffer pH 9.1 (25 mM), CTAB 30% (100 mM), and 1% butanol in methanol (70 : 30 : 5 v/v/v) with applied voltage of −10 kV using reverse polarity. The photodiode array detection was achieved at 225 nm. The linear calibration for each of the element was obtained within 0.16–10 𝜇g/mL with a limit of detection (LOD) 0.005–0.0167 𝜇g/mL. The separation and determination was repeatable with relative standard deviation (RSD) within 2.4–3.3% (𝑛=4) in terms of migration time and peak height/peak area. The method was applied for the determination of Mo(VI) from potatoes and almond, Ni(II) from hydrogenated vegetable oil, and Co(III) from pharmaceutical preparations with RSD within 3.9%. The results obtained were checked by standard addition and rechecked by atomic absorption spectrometry.